Jinbei oral liquid for idiopathic pulmonary fibrosis: a randomized placebo-controlled trial - Aijun Zhang; Kangkang Han; Fangfang Chen; Xiao Chen; Jun Wang; Yikai Niu; Zhaoqiu Hu; Chunyan Zheng; Liping Han; Zhaoqing Meng; Liangzong Zhang; Qingcui Xu; et al. (Scientific Reports)
Abstract The traditional Chinese medicine compound preparation known as Jinbei Oral Liquid (JBOL) consists of 12 herbs, including Astragalus membranaceus (Fisch.) Bge, Codonopsis pilosula (Franch.) Nannf, et al. Having been used for over 30 years in the treatment of pulmonary diseases, JBOL was evaluated in this study in order to assess its effect on idiopathic pulmonary fibrosis as well as its safety (ChiCTR2000035351, Chictr.org.cn.09/08/2020). A double-blind, multicenter, randomized, proof-of-concept trial was conducted to assess the efficacy of oral JBOL 40 ml and Corbrin Capsules 1 g compared to a placebo and Corbrin Capsules in patients with idiopathic pulmonary fibrosis (IPF). Over a 26-week period, patients received the active treatment or placebo three times daily, in a 1:1 ratio. This clinical study uses a randomized method, with a cycle of every 4 patients. TCM doctors at or above the deputy director level of the research center conduct TCM dialectics on IPF patients. To assess efficacy, over the duration of the trial, we measured serial changes in a composite indicator encompassing time to first acute exacerbation of IPF (first hospitalization or death due to respiratory cause), total lung capacity (TLC) (mL), predicted forced vital capacity (FVC%), forced vital capacity (FVC) (mL), predicted diffusing capacity of the lungs for carbon monoxide (predicted DLco%), 6-minute walk distance (6MWD), St. George’s Respiratory Questionnaire (SGRQ) total score, and arterial oxygen partial pressure (PaO2) from baseline to week 26 versus placebo. A total of 103 patients were screened, and 72 received the study medication. Of these, 68 patients were included in the analysis set, with 34 receiving JBOL and 34 receiving a placebo. After 26 weeks, a statistically significant reduction in total lung capacity (TLC) was observed for the JBOL group, with a change of 136 mL compared to -523 mL for the placebo group (difference 659 mL, 95% CI -1215 to -104 mL, p = 0.02). The study found that the change in FVC% predicted was − 1.48% and − 3.58% for the JBOL and placebo groups, respectively (difference of 2.10%, 95% CI -7.13 to 2.93, p = 0.41). Additionally the differences between the two groups in changes in FVC (mL), DLCO % predicted, PaO2 (mmHg) measures were − 67 mL (95% CI -238 to 104), -7.74% (95% CI -17.26 to 1.79), and − 3.57 mmHg (95% CI -10.02 to 2.87), respectively. Treatment with JBOL compared to placebo resulted in sequential changes in acute exacerbation, with no significant difference in SGRQ scores. It was not found that there was a statistically significant difference between the JBOL and placebo groups in TEAE reporting and serious TEAE reporting. Compared to the placebo group, there was a statistically significant reduction (p < 0.021) in TLC (mL) after 26 weeks for JBOL. The rates of FVC % predicted, FVC, DLCO % predicted, and PaO2 in the group treatment with JBOL were numerically lower than those in the placebo treatment group, although these differences did not reach statistical significance. JBOL exhibited comparable safety to placebo. This study has preliminarily shown the efficacy and safety of JBOL for IPF, but this is an exploratory clinical trial, more patient-involved studies should be needed in the near future. Trial registration: Chictr.org.cn ChiCTR2000035351; the trial was prospective clinical studies registered on August 9, 2020.